2017
DOI: 10.1016/j.annemergmed.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of the 2016 Consensus Definitions of Sepsis and Septic Shock on Future Sepsis Research

Abstract: Most ARISE participants did not meet the Sepsis-3 definition for septic shock at baseline. However, the majority fulfilled the new sepsis definition and mortality was higher than for participants not fulfilling the criteria. A quarter of participants meeting the new sepsis definition did not fulfill the qSOFA screening criteria, potentially limiting its utility as a screening tool for sepsis trials with patients with suspected infection in the ED. The implications of the new definitions for patients not eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Since the qSOFA score was developed, many people have evaluated its clinical value for sepsis. Some articles reported that the qSOFA as a good prognostic predictor [25,33], whereas other studies found that the qSOFA may not be an adequate screening tool in the ED because of its poor sensitivity [34][35][36]. A recent meta-analysis showed that the qSOFA was better than the SIRS was in predicting in-hospital mortality of sepsis [37], and a similar finding was observed in our cohort.…”
Section: Discussionsupporting
confidence: 82%
“…Since the qSOFA score was developed, many people have evaluated its clinical value for sepsis. Some articles reported that the qSOFA as a good prognostic predictor [25,33], whereas other studies found that the qSOFA may not be an adequate screening tool in the ED because of its poor sensitivity [34][35][36]. A recent meta-analysis showed that the qSOFA was better than the SIRS was in predicting in-hospital mortality of sepsis [37], and a similar finding was observed in our cohort.…”
Section: Discussionsupporting
confidence: 82%
“…The remaining 103 were discussed in a consensus meeting by CAG, MB, KH, LL, and RL. We included 45 papers in the final analysis [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59] (Figure 1). Excluded studies and the reasons for their exclusion are listed in Appendix G (Table A1).…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of post hoc analyses of randomized controlled trials and registry data report mortality rates greater than 40% when Sepsis-3 criteria are applied, [8][9][10] other data sets have also found lower than predicted mortality rates when applying the Sepsis-3 criteria. [11][12][13] The mortality rates for day 90 were comparable between the ADRENAL-APROCCHSS cohort and the original APROCCHSS cohort, although there was no different treatment effect between hydrocortisone and placebo in the ADRENAL. The other major difference between the ADRENAL and APROCCHSS was the use of fludrocortisone in the latter.…”
Section: Discussionmentioning
confidence: 99%